2022
DOI: 10.1007/s12671-022-02016-0
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based, Mindful, and Compassionate Parenting Training for Mothers Experiencing Parenting Stress: Results from a Pilot Randomized Controlled Trial of the Mindful Moment Program

Abstract: Objectives Mindful Moment is a self-guided, web-based, mindful, and compassionate parenting training for postpartum mothers who experience parenting stress. We aimed to assess Mindful Moment's feasibility, acceptability, and usability, and to gather preliminary evidence of its effectiveness in reducing parenting stress and outcomes such as mindful parenting, self-compassion, depressive symptoms, anxious symptoms, dispositional mindfulness, mother's perception of infant temperament, and mother-infant bonding. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 71 publications
0
5
0
1
Order By: Relevance
“…Three studies did not describe whether the interventions were delivered individually or as group-based interventions (Beaumont et al, 2012 ; Carlyle et al, 2019 ; Navab et al, 2019 ). A total of 23 studies involved self-compassion interventions administered online; 20 of these included interventions that ran in a web browser (Beshai et al, 2020 ; Cândea & Szentágotai-Tătar, 2018 ; Eriksson et al, 2018 ; Fernandes et al, 2022 ; Gammer et al, 2020 ; Guo et al, 2020 ; Hasselberg & Rönnlund, 2020 ; Kelly & Carter, 2015 ; Kelly et al, 2009 ; Kelman et al, 2018 ; Krieger et al, 2019 ; Lennard et al, 2021 ; Mifsud et al, 2021 ; Nadeau et al, 2021 ; Preuss et al, 2021 ; Shapira & Mongrain, 2010 ; Stevenson et al, 2019 ; Teale Sapach et al, 2023 ; Urken & LeCroy, 2021 ; Wong & Mak, 2016 ) and three studies administered interventions via a smartphone app (Al-Refae et al, 2021 ; Mak et al, 2018 ; Schnepper et al, 2020 ). Two studies involved self-compassion interventions that used self-help workbooks (Held & Owens, 2015 ; Sommers-Spijkerman et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies did not describe whether the interventions were delivered individually or as group-based interventions (Beaumont et al, 2012 ; Carlyle et al, 2019 ; Navab et al, 2019 ). A total of 23 studies involved self-compassion interventions administered online; 20 of these included interventions that ran in a web browser (Beshai et al, 2020 ; Cândea & Szentágotai-Tătar, 2018 ; Eriksson et al, 2018 ; Fernandes et al, 2022 ; Gammer et al, 2020 ; Guo et al, 2020 ; Hasselberg & Rönnlund, 2020 ; Kelly & Carter, 2015 ; Kelly et al, 2009 ; Kelman et al, 2018 ; Krieger et al, 2019 ; Lennard et al, 2021 ; Mifsud et al, 2021 ; Nadeau et al, 2021 ; Preuss et al, 2021 ; Shapira & Mongrain, 2010 ; Stevenson et al, 2019 ; Teale Sapach et al, 2023 ; Urken & LeCroy, 2021 ; Wong & Mak, 2016 ) and three studies administered interventions via a smartphone app (Al-Refae et al, 2021 ; Mak et al, 2018 ; Schnepper et al, 2020 ). Two studies involved self-compassion interventions that used self-help workbooks (Held & Owens, 2015 ; Sommers-Spijkerman et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 studies involved female participants only (Fernandes et al, 2022 ; Gammer et al, 2020 ; Guo et al, 2020 ; Kelman et al, 2018 ; Lennard et al, 2021 ; Mifsud et al, 2021 ; Nadeau et al, 2021 ; Navab et al, 2019 ; Noorbala et al, 2013 ; Savari et al, 2021 ; Seekis et al, 2020 ) while one study involved male participants only (Held & Owens, 2015 ). Of the 56 studies, 20 studies directly targeted people who reported psychological distress symptoms, such as depressive symptoms, anxiety, and stress (Anuwatgasem et al, 2020 ; Beshai et al, 2020 ; Bluth et al, 2016 ; Cândea & Szentágotai-Tătar, 2018 ; Collado‐Navarro et al, 2021 ; DeTore et al, 2022 ; Fernandes et al, 2022 ; Guo et al, 2020 ; Javidi et al, 2021 ; Kelly et al, 2009 ; Noorbala et al, 2013 ; Preuss et al, 2021 ; Savari et al, 2021 ; Schuling et al, 2020 ; Shapira & Mongrain, 2010 ; Stevenson et al, 2019 ; Teale Sapach et al, 2023 ; Torrijos‐Zarcero et al, 2021 ; Urken & LeCroy, 2021 ; Yadavaia et al, 2014 ). Two studies directly targeted individuals with low levels of self-compassion (Arimitsu, 2016 ; Yadavaia et al, 2014 ), and two studies directly targeted adults with high levels of self-criticism (Krieger et al, 2019 ; Shahar et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Son yıllardaki alanyazında bu konunun önemle ele alındığı görülmektedir. Örneğin yapılan bir çalışmada (Fernandes, Monteiro, Canavarro ve Moreira, 2022) Mindful Moment (Dikkatli An veya Anın Farkındalığı) gibi eğitimler sunularak ebeveynlerin merhametli tutumlarının artırılması hedeflenmektedir. Bu şekilde bir tarafta ebeveynlik stresiyle ilişkili semptomlar azaltılabilmekte diğer tarafta ise ebeveynlerin dikkatlerinin yanı sıra merhametli tutumlarına katkı sağlanabilmektedir.…”
Section: Ebeveynlik Programlarıunclassified
“…To address these structural, societal, and individual barriers, internet-based interventions (IBIs) have emerged as a recognized and easily accessible means of providing specialized therapeutic care to women with the potential to both prevent and treat postpartum depressive symptoms [ 19 21 ]. IBIs targeting PPD commonly use evidence-based treatment elements, such as CBT techniques including behavioral activation and cognitive restructuring [ 22 24 ], psychoeducational components [ 24 – 26 ], and mindfulness and self-compassion practices [ 24 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%